Safety and efficacy of quick-soluble gelatin microparticles for transarterial embolization of the lower urinary tract: Preclinical study in a rabbit urinary bladder embolization model - Sunghoon Jeon; Keunho Kim; Cheolwon Choe; Juil Choi; Gun Lee; Chung-Do Lee; Hyeon-Jeong Moon; Jun-Gyu Park; Jin-kyung Kim; Namsoon Lee; Dongwoo Chang (PLoS ONE, 2025)
Quick-soluble gelatin microparticles (QS-GMP) are emerging embolic agents under investigation for temporary vascular occlusion, offering reduced ischemic risk compared to permanent materials. The aim of this preclinical study was to evaluate the safety and efficacy of QS-GMP for transarterial embolization in a rabbit model of urinary bladder embolization. Twelve male New Zealand White rabbits underwent bilateral umbilical artery embolization using QS-GMP. Animals were assigned to four time-points (immediately, 3, 7, and 14 days post-embolization), with comprehensive assessments including clinical observations, hematologic and serum biochemical analysis, angiography, and histopathology. The procedure was technically feasible in all animals without intraoperative complications. Temporary hematuria and a transient decrease in body weight were observed post-procedure, both of which resolved spontaneously. Complete occlusion of the cranial vesical artery and absence of bladder wall perfusion were achieved immediately after embolization, followed by full recanalization at 3 days. Angiographic imaging at 7 and 14 days revealed transient hypervascularization of the bladder wall. Histopathological analysis showed marked edema, epithelial necrosis, and inflammatory infiltration at 3 and 7 days, with full urothelial regeneration observed at 14 days. No signs of ureteral or renal injury, or adverse systemic responses were detected. These findings suggest that QS-GMP may serve as a feasible option for temporary arterial occlusion in future veterinary lower urinary tract applications, although further long-term evaluation is warranted.